Student Vitality, Teacher Engagement, and Rapport in Studio Music Instruction - Blackwell, Jennifer; Miksza, Peter; Evans, Paul; McPherson, Gary E. (Frontiers in Psychology, 2020)
Vitality is the feeling of being alive, vigorous, and energetic, and is an important indicator of overall motivation and wellbeing. Studio music instruction holds rich potential for creating feelings of vitality through close relationships, the potential for developing skills, and a shared endeavor of artistic expression. But they also have the potential to deplete vitality—through controlling teaching, a poor quality relationship, or harsh criticism from the teacher. The purpose of this study was to investigate relationships among student and teacher behavior, rapport, and students’ experiences of subjective vitality in the context of university-level applied performance lessons. Participants were six undergraduate instrumental music majors and their teachers located at universities in the United States and Australia, who were selected because they provided the highest (three participants) and lowest (three participants) scores on a measure of subjective vitality completed immediately following a studio music lesson. A lesson was recorded for each student-teacher participant pair, coded for the frequencies of 35 lesson behaviors, described with a qualitative contextual commentary, and rated for evidence of rapport and physical proximity. Clear differences emerged between the high and low vitality lessons with regard to questioning, feedback, modeling, student performance, and student talk. Teachers of high vitality students spent most or all of the lesson within close proximity to their student, and showed stronger rapport than teachers of low vitality students. The findings suggest that students’ vitality may depend on important differences in styles of teacher-student engagement and the quality of student-teacher relationships.